1984
DOI: 10.1017/s0003356100027628
|View full text |Cite
|
Sign up to set email alerts
|

The effect of type of concentrate and level of concentrate feeding on milk production

Abstract: Twenty-four British Friesian dairy cows in early lactation were used in a change-over design experiment with three periods, each of 4 weeks duration. The aim of the experiment was to assess the effects of both the type of concentrate and the level of concentrate supplementation on the utilization of grass silage for milk production. Four treatments consisted of offering 10 kg/day of either a barley (10B) or a sugar beet pulp-based concentrate (10S), each concentrate being offered at two crude protein concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
102
3
2

Year Published

1987
1987
2008
2008

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(129 citation statements)
references
References 24 publications
21
102
3
2
Order By: Relevance
“…Castle et al 1981, Mayne and Gordon 1984, Phipps et al 1987, Sloan et al 1987 no differences have been found between starchy and fibrous concentrates in their effect on milk yield.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Castle et al 1981, Mayne and Gordon 1984, Phipps et al 1987, Sloan et al 1987 no differences have been found between starchy and fibrous concentrates in their effect on milk yield.…”
Section: Discussionmentioning
confidence: 97%
“…In the previous trial (Huhtanen et al 1988), increasing the proportion of barley fibre in the diet increased silage DM intake markedly but the effect was mainly offset by the reduced intake of supplement. Likewise, when small or moderate levels of concentrate have been used, the effect of concentrate energy source on silage DM intake has been relatively small (Castle et al 1981, Mayne and Gordon 1984, Sloan et al 1987, Huhtanen 1987. On the other hand, Thomas et al (1986) reported that cows given high levels of supplement based on unmolassed sugar beet pulp and rice bran ate 0.9 kg/day more silage DM than those given barley based supplements.…”
Section: Discussionmentioning
confidence: 99%
“…However, often the higher NDF digestibility with fibrous by-products can be attributed to differences in the intrinsic characteristics of concentrate fibre fraction rather than to improved forage NDF digestibility (Mayne and Gordon, 1984;Huhtanen, 1988;Sutton et al, 1993). In the study of Huhtanen (1988), diet NDF digestibility was markedly higher with sugar beet pulp supplements compared with barley supplements, but there were no differences in the ruminal in situ digestion kinetic parameters of forages.…”
Section: Concentrate Supplementationmentioning
confidence: 95%
“…In view of the similar substitution rate they suggested that the increase in forage intake was not mediated solely by changes in fibre digestion in the rumen. Chamberlain et al (1984) found a different response in silage intake when they modifyed the composition of supplement, and their data indicate that higher intakes with SBP can be expected only with highly digestible silage and high concentration of total N. In contrast to this, Mayne and Gordon (1984) reported with highly digestible silage (D-value 0.691) a significantly lower silage DM intake on SBP than on Ba. In the present study the D-value of silage was 0.622, similarly to the studies of Under other circumstances, in grazing cattle (Meus 1986) or with high levels of concentrate in hay based diets (Sutton et al 1984), forage intakes has been higher in cows given concentrates based on fibrous by-products than in those given starchy concentrates.…”
Section: Feed Intakementioning
confidence: 98%
“…Reduction in the rate and extent of forage digestion, slowing the passage of digesta, will result in decreased forage intake. Replacing starchy supplements by fibrous supplements has widely been reported to increase the digestibility of different fibre components (Mayne and Gordon 1984, Sutton et al 1985, Thomas et al 1986. Fahmy et al (1984) reported a smaller decrease in the disappearance of ammoniatreated straw from nylon bags in sheep receiving sugar beet pulp than in sheep receiving barley with increasing levels of supplementation.…”
Section: Introductionmentioning
confidence: 99%